الدور الوسيط لجودة الخدمات الصحية في العلاقة بين إدارة الجودة الشاملة ورضا العملاء دراسة حالة مركز طرابلس الطبي ليبيا: The Mediating Role of the Quality of Health Services on the Relationship between Total Quality Management and Customers Satisfaction: Case Study of Tripoli Medical Centre – Libya - رابعة عويدات عبد الجليل; نهج عبدالمجيد علوي (Journal of North African Economies, 2025)
The aim of this study is to determine the direct effect of Total Quality Management on customer satisfaction, and the indirect effect through the quality of health services at Tripoli Medical Center in Libya. To achieve the goal of the study, a questionnaire was designed based on previous related studies to collect data from the study sample. The study sample consisted of 391 employees at Tripoli Medical Center in Libya, as well as 391 customers who see doctors at the same center. The study found a statistically significant positive relationship between Total Quality Management and customer satisfaction, and a statistically significant impact of quality of health services as a mediator in the relationship between Total Quality Management and customer satisfaction in Tripoli Medical Center, Libya. The study provided a number of recommendations, the most important of which are: focusing on applying the concept of Total Quality Management by focusing on customers, researching their preferences and working to meet them and solving problems as soon as possible, as this enhances customer satisfaction. Improving and developing the quality of health services through Total Quality Management such as supporting top management, continuous improvement of internal methods and processes, and focusing on customers.